Functional Testing of Subcutaneous Piezoelectrically Actuated Hearing Aid: Comparison With BAHA and Potential for Treating Single-sided Deafness. Issue 6 (July 2016) - Kotiya, Akhilesh; Bance, Manohar; Leadbetter, Jeff; Brown, Jeremy; Adamson, Rob
Abstract : Objective: To compare the performance of a subcutaneous piezoelectrically actuated hearing aid (SPAHA) with the bone-anchored hearing aid (BAHA) and assess its effectiveness as a treatment option for conductive loss and single-sided deafness (SSD). Background: To validate the use of the SPAHA as a bone conduction implant, its performance was compared with a widely used bone conduction implant, the BAHA. Maximum dynamic range, power consumed to deliver standard speech signals and total harmonic distortion (THD) was assessed. The transcranial attenuation was also measured to assess the SPAHA's potential to treat SSD. Method: Functional testing of the SPAHA and BAHA was conducted using cadaver heads. Ipsilateral and contralateral promontory velocity and the power consumption by the devices were measured at 111 different frequencies in the range of 200 to 9600 Hz. Performance metrics were derived from these measurements. Result: The maximum dynamic range for SPAHA was within 10 dB of that of BAHA. The THD for the SPAHA was at most 3%, slightly better than the BAHA. The power consumption by the SPAHA, whereas highly variable, was not statistically different than that of the BAHA. Transcranical attenuation in case of SPAHA was 5 to 10 dB across the measured frequency range. Conclusion: From observed dynamic range and THD, the speech quality delivered by the SPAHA should equal or exceed that delivered by the BAHA. To attain equivalent hearing sensation at lower frequencies, the drive voltage for SPAHA would have to be significantly higher than that for BAHA. For typical speech inputs the power consumption requirements of the SPAHA should be roughly equal to those of the BAHA. Given its performance at high frequencies, the SPAHA seems well-suited to treating SSD.